Network monitoring : asset discovery application software - Tan, Jun Han (2017)
Since the past few decades, Ethernet networks have undergone impressive growth in terms of the equipment such as switches, routers, and links, that have been added, as well as the number of users that it supports. This greatly escalated the security threats to the network because any unsecured devices connected to the network may be used as an entry point to gain access into the network by hackers. Hence, network topology information is immensely valuable especially for network security, but it is also useful for other purposes, such as performance prediction, administration, and management. In the recent years, manual network mapping is getting increasingly difficult because of the ever-changing size and dynamic behavior of networks. Therefore, automatic network topology discovery tools and algorithms are becoming increasingly crucial. This project involved developing an asset discovery application software for automatic network topology discovery, and discusses on the methodology behind the application. Furthermore, this report shows and discusses on the results obtained from implementing the application on both virtualized and physical networks. Lastly, this report also includes about the limitations of the application and the possible future works to overcome those limitations.